Body Mist-Making Training and Socialization of Cosmetic Product Registration and Marketing Authorization to Youth Organisations in Kerinci - Nova Syafni; Try Andy Sahputra; Saafrida Saafrida; Uswatul Hasanah; Rini Agustin; Rahmi Yosmar; Friardi Ismed; Erizal Zaini (Warta Pengabdian Andalas, 2024)
Indonesia is an important country that produces essential oils that are widely used in fragrance cosmetic products. The use of local essential oils for cosmetics needs to be introduced to the youth generation with the aim that they do not just become consumers. Youth organisations in Kerinci have many activities to improve their skills and abilities for a better future. Collaboration between the university and the youth organisation was achieved by providing training on doing cosmetic product training on making cosmetic products. The product uses essential oils called body mist. Nowadays, the youth still know very little about the manufacturing process of cosmetics products. To provide further benefits, this community service activity collaborated with BBPOM in Padang, West Sumatra, to explain cosmetic safety and the registration process of cosmetic products. With this series topic in this training and outreach-related cosmetics, it is hoped that it can increase business ideas for young people who are members of the Sakti Alam Kerinci Organisation.